Czech Republic : Selected Issues. (IMF Staff Country Reports; Country Report, 1999)
This Selected Issues paper on the Czech Republic discusses issues relating to the enterprise sector and corporate governance. This includes an overview and assessment of enterprise performance along with a discussion of the concept of corporate governance and its application in the Czech Republic, including how corporate governance practices compare in an international context. The paper discusses issues related to financial sector performance and restructuring. It also takes stock of banking sector developments and performance and reviews financial policy and supervisory challenges, including the definition of policies for bank privatization and the appropriate prudential framework.